KOMPETENSI PEDAGOGIK GURU BAHASA ARAB DI PONDOK PESANTREN: STUDI KASUS IMPLEMENTASI BI’AH LUGHAWIYYAH - Friscilla Wulan Tersta; Helmun Jamil; Muhammad Najib (STKIP Subang, 2026)
The pedagogical competencies of Arabic language teachers are a crucial factor in the success of learning, particularly in Islamic boarding schools that implement a 24-hour language immersion system (bi’ah lughawiyyah). This study aims to describe the pedagogical competencies of Arabic language teachers and to identify the supporting and inhibiting factors at the Al Ikhwan Islamic Boarding School in Muaro Jambi. The study employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation of three Arabic language teachers selected via purposive sampling. Data validity was ensured through triangulation of sources and techniques, while data analysis followed an interactive model. The results indicate that teachers’ pedagogical competencies generally fall into the adequate to good category, though they are not yet optimal. Understanding of students’ characteristics is fairly good, but the implementation of differentiated instruction remains limited. Instructional planning is beginning to align with the Merdeka Curriculum; implementation is dominated by lecture-based methods with minimal use of digital media; and assessment remains focused on cognitive aspects. The main supporting factors are the bi’ah lughawiyyah program and student motivation, while inhibiting factors include time constraints, a lack of pedagogical training, insufficient facilities, and the absence of academic supervision. This study recommends strengthening the teacher mentoring system and developing a pedagogical competency model that is contextual to Islamic boarding schools.